2021
DOI: 10.32734/psikologia.v15i2.4893
|View full text |Cite
|
Sign up to set email alerts
|

Fear of missing out and cyberloafing among college students

Abstract: English This research examines the effects of fear of missing out on cyberloafing. Individuals who experience fear of missing out are afraid to miss a pleasant experience. The individual will try to stay connected with others through social media. The study hypothesized that fear of missing out would be positively related to cyberloafing, which refers to behavior of accessing the internet for non-academic activities. As expected, the results show that fear of missing out accounted for about 22 per cent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As for the reliability coefficients of each dimension, the analyses showed that the reliability coefficient of the first dimension (items 1-9) is .93. The second dimension (items 10-16) has a reliability coefficient of .87 and the third dimension (items17-21) .93, the fourth dimension (items [22][23][24][25][26] .94 and the fifth dimension (items 27-30) .80. The reliability coefficient for the overall scale was calculated as .95 [25].…”
Section: Cyberloafing Scalementioning
confidence: 99%
See 1 more Smart Citation
“…As for the reliability coefficients of each dimension, the analyses showed that the reliability coefficient of the first dimension (items 1-9) is .93. The second dimension (items 10-16) has a reliability coefficient of .87 and the third dimension (items17-21) .93, the fourth dimension (items [22][23][24][25][26] .94 and the fifth dimension (items 27-30) .80. The reliability coefficient for the overall scale was calculated as .95 [25].…”
Section: Cyberloafing Scalementioning
confidence: 99%
“…Therefore, cyberloafing is considered to be an obstacle while integrating information technologies and education [17]. In educational environments, cyberloafing correlates with various variables such as academic motivation [18], academic performance level [19], nomophobia [20], perceived stress [21], productivity [22], fear of missing-out [23], academic flow [24]. In addition, there are some studies aiming to determine the reasons of these behaviors in educational institutions [15,25,26].…”
Section: Introductionmentioning
confidence: 99%